Geographical patterns and current and short‐term historical correlates of phylogenetic diversity and endemism for New World primates. (26th December 2019) - Varzinczak, Luiz H.; Zanata, Thais B.; Moura, Mauricio O.; Passos, Fernando C.
Abstract: Aim: Addressing the phylogenetic relationship among species has been insightful to understand evolutionary and biogeographical processes shaping the distribution of diversity across broad geographical gradients. Here we determine the geographical distribution and the variables correlated with the phylogenetic component of diversity and endemism for primates, as well as their relationships with the taxonomic component of diversity. Location: New World. Taxon: New World monkeys, Platyrrhini . Methods: We mapped primate occurrence in cells of 110 × 110 km. For each cell, we calculated phylogenetic diversity (PD) and endemism (PE), as well as how much these indices deviate from their expected values based on species richness (SR) and endemism (SE), respectively. Using simultaneous autoregressive models, we tested the effects of mean annual temperature, forest structure and climate history on the current patterns of primate phylogenetic diversity. Results: We found that most primate phylogenetic diversity is found in the tropical forests of South America. Tropical forests also present much higher PD and PE than predicted by SR and SE, respectively, demonstrating their importance in producing and maintaining primate phylogenetic diversity in the New World. Furthermore, regions presenting low SR and SE nevertheless show high PE, likely because these areas have witnessed the evolution of many clades occurring exclusively therein. Overall, mean annual temperature had the highest influence in explaining phylogenetic indices. Main conclusions: Our results suggest a strong influence of primate biogeography throughout the New World on the geographical distribution of the phylogenetic component of their diversity, with the Amazon, Atlantic Forest and Central America containing the greatest amount and endemism of phylogenetic diversity. Our study contributes to a better understanding of the dynamics underlying the geographical distribution of New World's primate diversity, especially in a phylogenetic context in which their biogeographical history has deeply affected current patterns of primate diversity in this region. Our results provide essential information for the conservation of primate evolutionary history, especially considering the forecast effects of habitat loss and climate change on the dynamics of tropical forests.